Pengaruh E-Worksheet terhadap Kemampuan Pemecahan Masalah Matematika Berdasarkan Motivasi Belajar Siswa - Eriana, Sabila; Harini, Esti; Kusumaningrum, Betty (Indonesian Journal of Teaching and Learning, 2023)
This study aims to evaluate the differences in problem-solving abilities among students with low, moderate, and high motivation levels, as well as to compare the problem-solving abilities between students who use and do not use e-worksheet. Data analysis was conducted using prerequisite tests, t-test, and ANOVA hypothesis test. The results of the study indicate that there are differences in problem-solving abilities among students with low, moderate, and high motivation levels. Additionally, there are differences in problem-solving abilities between students who use and do not use e-worksheet. However, no significant interaction was found between the use of e-worksheet and learning motivation on students' problem-solving abilities.